Prelinguistic and Minimally Verbal Communicators on the Autism Spectrum - Keen, Deb; Meadan, Hedda; Brady, Nancy C.; Halle, James W. (Springer Nature Singapore : Imprint: Springer, 2016)
This book draws on contemporary theory and recent findings to provide researchers, professionals, undergraduate and graduate students with essential resources, allowing them to better understand and support children, youth and adults with autism and significant communication impairments. The book consists of 11 chapters organized into 3 sections detailing typical and atypical prelinguistic development for individuals on the autism spectrum, together with a range of assessment and intervention approaches that clinicians and educators can draw on in practice. The book adopts a lifespan perspective, recognizing that there is an important and particularly challenging sub-group of children on the spectrum who remain minimally verbal beyond the age of 8 years. Each chapter summarizes current research on a selected topic, identifies key challenges faced by researchers, educators and clinicians, and considers the implications for research and practice. The concluding chapter considers issues of research translation and how educators and clinicians can encourage the use of evidence-based practices for prelinguistic and minimally verbal individuals.